NUTRITION AND HEALTH POLICIES FOR THE CHILDREN IN UTTAR PRADESH - Shivangi (International Journal of Research -GRANTHAALAYAH, 2019)
Human resource is one of the greatest strength of our country. However, poverty and unemployment lead to an increase in health problems and diseases. Government’s Health policy enables to direct the attention towards the key problem. Uttar Pradesh has the highest number of malnourished children, thus making the State most under-nourished state of the country. With the use of diverse sources i.e. government reports and records, newspapers etc, explore the state policies in eradicating under nutrition among the children and analyse the impact of these policies in improving the nutritional status and reducing the child mortality and morbidity in the State. Together with this, analysis of the nutrition programmes such as State’s Nutrition Mission, Mid- day Meal scheme and its impact will also be studied here. The poor state of nutrition of children is due to lack of comprehensive policy, low nutrition budgeting but above all the gap in implementation of State’s Nutrition Mission Program and other schemes at ground level.